Implementation of the Problem Based Learning (PBL) Learning Model to Improve Chemistry Learning Outcomes in Vocational Schools - Siti Wulan Dari; Hartono Hartono; Rahman Susanto (Pedagogy Review, 2023)
Abstract: Implementasi Problem Based Learning Model to Improve Chemistry Learning Outcomes in SMK .This classroom action aimed to improve the learning chemistry achievement of class X students at SMK Negeri 4 Palembang through Problem based learning model specifically TKR 3class. This research was carried out in teo cycles, each cyscle consisted of two meetings. The data were obtained by using observation sheet and students’ learning achievement test which was conducted at the end of the meeting. The improvement of students’ achievement could be seen from the students’ learning achievement average. The students’ learning achievement average before the action was 59,44 with learning completeness was 38,89%. The improvement in cycle 1 was up to 70,55 with learning completeness 66,67% and cycle II improved up to 84,44with learning completeness was 86,11 %.Keywords: learning, action, research, problem